International Days of Statistics and Economics 2019 2019
DOI: 10.18267/pr.2019.los.186.171
|View full text |Cite
|
Sign up to set email alerts
|

Does a difference in the motivation of volunteers and other people exist?

Abstract: Humanitarian workers operate in complex environments with various challenges and demanding working conditions. These challenges put aid workers in a range of risks and under the pressure. However, human resources are crucial for success of humanitarian operations in general. At the same time, each humanitarian operation is reliant on logistics and logistics activities are always connected with logistic staff. Understanding what motivates logisticians to join the humanitarian sector is essential information for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…If it will be included aspects or factors like an age, a gender, a repetition of research, it could lead to other interesting results. It is possilbe to suppose that the peronality types for example MBTI test also influence research results [38]. In this research, the theoretical thinking of respondents in specific time was observed.…”
Section: Discussionmentioning
confidence: 83%
“…If it will be included aspects or factors like an age, a gender, a repetition of research, it could lead to other interesting results. It is possilbe to suppose that the peronality types for example MBTI test also influence research results [38]. In this research, the theoretical thinking of respondents in specific time was observed.…”
Section: Discussionmentioning
confidence: 83%
“…Formal volunteering is organized. Examples of volunteer work include election activities, community events, religious activities, the environment, working with animals, and assistance with people with special needs, adult education and fundraising [22]; [5].…”
Section: The Willingness To Work and Motivation Of Volunteermentioning
confidence: 99%
“…This article focuses on the impact of volunteers' previous experience with volunteering, specifically by managing volunteering on projects in terms from the point of view of volunteer age and willingness to participate in volunteering in the Czech Republic repeatedly. The results of Zárubová, & Švecová [5]; [6]; [7] point to the motivation of volunteers in terms of various factors. It was confirmed that it cannot be ruled out that the motivation of volunteers and other people is different [5], further that the motivation of volunteers is connected with study [6] and that the targeting of volunteers and other people is different [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They can be internal and external. They spoke about fundraisers, volunteers in many roles (Zárubová, & Švecová, 2019a;2019b;, project preparation helpers, project realizations helpers (paid and volunteers), designers, administrators etc.…”
Section: Supported Projects From European Fundsmentioning
confidence: 99%